Wayang dan Bahasa sebagai Strategi Visual dalam Desain Produk Grafis: Identitas dan Narasi Budaya dalam Visual Kontemporer Indonesia - Saban, Zulfikar; Noorsasetya, Ananta Hari (Faculty of Arts and Design, Jakarta Institute of the Arts, 2026)
This study examines the role of wayang and language as visual strategies in graphic product design, particularly in shaping visual identity and cultural narratives within the context of contemporary Indonesian visual culture. In the practice of visual communication design, wayang is generally understood as a representation of traditional culture, while language is positioned as a verbal element for conveying messages. However, with the development of the creative industry, both have undergone a transformation into visual elements that play a strategic role in building product identity and visual differentiation. This study aims to analyze how wayang and language are represented as visual elements in graphic product design, as well as how both function as visual strategies in shaping a product’s identity and cultural narrative. The study employs a qualitative approach using visual analysis and visual semiotics. The research subjects consist of T-shirt designs featuring wayang illustrations (Hanoman, Gatotkaca, and Petruk) combined with local languages, including Walikan and Javanese. Research findings indicate that wayang has undergone a visual transformation from its traditional form to contemporary graphic illustrations through processes of stylization, simplification, and visual exploration. Meanwhile, language functions not only as text but also as a visual element that shapes composition, identity, and cultural meaning. The combination of wayang and language produces a dual visual strategy that reinforces local identity, creates product differentiation, and builds a cultural narrative relevant to the contemporary visual context. This research contributes to the academic development of visual communication design by proposing the concepts of wayang and language as visual strategies in graphic product design, and by expanding the understanding of the role of graphic products as a medium for cultural identity and representation in the creative industry.